Livestock and fish production, consumption of animal-sourced foods, and climate change to 2050 - Supplementary global data on livestock feed biomass supply - Enahoro, Dolapo; Wiebe, Keith; Oloo, Stephen; Devulapalli, Ravi; Komarek, Adam; Herrero, Mario; Sircely, Jason; Boone, Randall (2024)
Enhance and apply the IMPACT system of models to examine multiple and likely conflicting trends and related goals at the global and regional scales, and for selected countries, in the context of changes in population, income, technology and climate to 2050. This dataset is directly applicable for use as the baseline feed data for the global economic model IMPACT. It is adaptable for use with models with similar representation of the global agricultural and food system.